3D-heterostructured NiO nanofibers/ultrathin g-C3N4 holey nanosheets: An advanced electrode material for all-solid-state asymmetric supercapacitors with multi-fold enhanced energy density. (20th October 2020) - Paliwal, Mahesh Kumar; Meher, Sumanta Kumar
Highlights: Highly hydrophilic and holey g-C3 N4 (GCN) nanosheets are prepared by one-step method. GCN nanosheets are used as the conductive substrate to grow flaccid NiO nanofibers. The 1.8 V NiO/GCN||N-rGO delivers 3-times more specific capacitance over NiO||N-rGO ASSASC device. After 6000 GCD, NiO/GCN||N-rGO shows 13.4% more specific capacitance retention over NiO||N-rGO ASSASC device. At high power density, NiO/GCN||N-rGO delivers 6-times more energy density over NiO||N-rGO ASSASC device. Abstract: Herein, we report a modified polyol condensation based synthesis of highly-hydrophilic, lowly-crystalline and holey-ultrathin g-C3 N4 (GCN) nanosheets, which are further used as the conducting matrix to interfacially grow NiO nanofibers. The physicochemical studies show restricted crystal growth of NiO on GCN, ultra-dispersive nature of NiO/GCN heteronanocomposite in water, and chemical interaction between NiO and GCN. Thorough electrochemical analyses in 3-electrode setup confirm lower equivalent series resistance, charge transfer resistance and diffusion resistance of NiO/GCN heteronanocomposite as compared to pristine NiO. The NiO/GCN heteronanocomposite offers 2 times more specific capacitance and higher rate capacitance as compared to the pristine NiO. Further, 1.8 V all-solid-state asymmetric supercapacitor (ASSASC) devices are fabricated by using NiO/GCN heteronanocomposite and pristine NiO as the positive electrode materials, and N-rGO as the negative electrode material, and the supercapacitive charge storage efficiencies of the devices are systematically compared. Results show that, the respective mass-specific capacitance and rate capacitance offered by NiO/GCN||N-rGO is 2 and 3 times more than that offered by pristine-NiO||N-rGO ASSASC device. The NiO/GCN||N-rGO also offers 2.7 and 6 times more energy densities at respective power densities of 3200 and 6900 W kg –1, over pristine-NiO||N-rGO ASSASC device. Further, the NiO/GCN||N-rGO retains 13% more specific capacitance as compare to the pristine-NiO||N-rGO ASSASC device, after 6000 charge-discharge cycles. The largely improved supercapacitive charge storage efficiency of NiO/GCN heteronanocomposite is ascribed to GCN-prompted surface functionality, lowly-impeded electron transport, and greater electrolyte access to the majority of redox-active sites, during high-rate supercapacitive charge storage process. Graphical abstract: Image, graphical abstract